Ginsenoside Rh2 impedes proliferation and migration and induces apoptosis by regulating NF‐κB, MAPK, and PI3K/Akt/mTOR signaling pathways in osteosarcoma cells. Issue 12 (6th August 2020) - Li, Chenchen; Gao, Huan; Feng, Xuemei; Bi, Chuyao; Zhang, Jing; Yin, Jianyuan
Abstract: Ginsenoside Rh2 is a primary bioactive compound obtained from ginseng that indicated anticancer activities against several malignant tumors. However, previous studies have reported little about the inhibitory effect of Rh2 on osteosarcoma (OS). This study aims to explore whether Rh2 could exert anticancer effects in OS cells and further investigate the proliferation, migration, and apoptosis mechanisms induced by Rh2 in human OS U20S cell line. The viability of U20S cells was obtained by the 3‐(4, 5‐dimethyl‐2‐thiazolyl)‐2, 5‐diphenyl‐2‐H‐tetrazolium bromide assay. Cell migration property was analyzed by wound‐healing assay. Apoptosis was visualized using terminal deoxynucleotidyl transferase dUTP nick‐end labeling (TUNEL), 4′, 6‐diamidino‐2‐phenylindole (DAPI), and annexin V/propidium iodide (PI) staining. Relative protein expressed was confirmed through Western blot analysis. Mitochondrial membrane potential was evaluated by JC‐1 staining. In this study, we used broad‐spectrum anticancer drug cisplatin (CP) as a positive control. The results indicated that Rh2 remarkably inhibited cell viability of U20S cells in a dose‐ and time‐dependent manner, and suppressed migration. TUNEL, DAPI, annexin V/PI, and JC‐1 assay suggested that Rh2 could induce cellular apoptosis. Rh2 could reduce the levels of Bcl‐2, caspase 3, and caspase 9, and promote the expression level of Bax in U20S cells. Moreover, Rh2 could induce apoptosis by promoting mitogen‐activated protein kinase (MAPK) signaling pathway and inhibit PI3K/Akt/mTOR and nuclear factor‐κB (NF‐κB) signaling pathway in U20S cells. These findings indicated that Rh2 has an anticancer effect on U20S cells by regulating MAPK, PI3K/Akt/mTOR, and NF‐κB signaling pathway.